2017
DOI: 10.9790/0853-1601037580
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological Spectrum of Lesions in Fallopian Tube

Abstract: Background: Fallopian tube is a common specimen in the laboratory. It is affected by a wide spectrum of diseases but there are only occasional studies, documenting histological changes in the fallopian tube removed for all reasons. Aims and objectives:To study the gross and microscopic features of the excised fallopian tubes and to study the common and unusual lesions in them. To find the incidences of tumour and the tumour like lesions of the fallopian tube. Materials and Methods: A sample size of 200 cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 4 publications
(9 reference statements)
1
3
1
Order By: Relevance
“…The Incidence of endometriosis is slightly higher as compared to other studies. (Pratima kujur, et al 2016) [47] Other non neoplastic lesions are seen in this study are decidual reaction (4%), Walthard Nests (10%) and Walthard Nests with cystic change (5%) which are slightly higher than other studies done by Prachi Kukreja et al (2017) [43] . Incidence of paratubal cyst (Para mesonephric cyst 7% Mesonephric cyst 4% and Mesothelial cyst 5%) which is almost same as studies done by Prachi Kukreja et al (2017) [43] , Mehnaz Choudhury et al (2019) [49] and Pratima Kujur et al (2016) [47] .…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…The Incidence of endometriosis is slightly higher as compared to other studies. (Pratima kujur, et al 2016) [47] Other non neoplastic lesions are seen in this study are decidual reaction (4%), Walthard Nests (10%) and Walthard Nests with cystic change (5%) which are slightly higher than other studies done by Prachi Kukreja et al (2017) [43] . Incidence of paratubal cyst (Para mesonephric cyst 7% Mesonephric cyst 4% and Mesothelial cyst 5%) which is almost same as studies done by Prachi Kukreja et al (2017) [43] , Mehnaz Choudhury et al (2019) [49] and Pratima Kujur et al (2016) [47] .…”
Section: Discussioncontrasting
confidence: 41%
“…Incidence of hydrosalpinx is 3% and hematosalpinx is 2% in this study. Prachi et al [43] and Bagwan IN et al [4] found tubal epithelial hyperplasia in 1.34% and 0.29% of cases respectively. In our study, tubal epithelial hyperplasia is seen in 3% cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prachi et al 21 and IN Bagwan et al 11 had tubal epithelial hyperplasias of 1.34% and 0.29% respectively in concordance with our study, which had higher incidence of 2.1%.…”
Section: Discussionsupporting
confidence: 91%
“…Our study was in concordance with other studies. Prachi et al, 21 Deepthi et al, 22 Gon S et al, 16 Jha R et al, 20 IN Bagwan et al, 11 Jennifer L. and Hunt et al, 2 all the studies had normal histology cases outnumbered the cases with tubal pathology.…”
Section: Discussionmentioning
confidence: 99%